1976
DOI: 10.1079/bjn19760108
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of zinc supplementation against copper toxicosis in sheep

Abstract: I . A study has been made of the effects of dietary zinc supplementation on the development of copper toxicosis in three groups each of eight 12-week-old lambs.2. None of the lambs receiving 420 mg Zn/kg diet developed Cu toxicosis in the z4-week experimental period, compared with three in the control group receiving 43 mg Zn/kg and possibly one in the group receiving 220 mg Zn/kg. 3.Liver Cu concentrations were reduced by up to 40 % in the Zn-supplemented animals, with concomitant reductions, especially in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…Zn and Cu are mutual antagonist trace elements and there is a competitive biological interaction between them (Bremner et al 1976;Bremner et al 1995). Although changes in the activity of Cu enzymes may occur in animals or in cells exposed to high levels of Zn, it is not certain that Cu in the enzymes is displaced by Zn, rather it seems that the amount of Cu has been reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Zn and Cu are mutual antagonist trace elements and there is a competitive biological interaction between them (Bremner et al 1976;Bremner et al 1995). Although changes in the activity of Cu enzymes may occur in animals or in cells exposed to high levels of Zn, it is not certain that Cu in the enzymes is displaced by Zn, rather it seems that the amount of Cu has been reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Zn supplements reduce the incidence of Cu toxicosis in sheep (Bremner et al 1976) and are now used to treat Wilson's disease in humans (Hoogenraad et al 1978;Brewer et al 1983). Brewer et al (1993) have established the optimumdosage regimen to reduce Cu absorption and to restore Cu balance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when combined with supplements of S and Mo, bentonite might bind the S and Mo supplements in the rumen and decrease their effectiveness in reducing the bioavailability of dietary copper (Ivan et al, 1999). Therefore, the remaining dietary supplements that reduce the dietary Cu bioavailability are Mo, S, Zn and Fe (Dick, 1954;Ross, 1966 and1970;Hogan et al, 1968;Suttle, 1974 and1975;Bremner et al, 1976;Phillipo et al, 1987). Owing to the fact that the concentration of Fe in PKC is known to range between 800 and 6000 mg/kg DM and was 1512 mg/kg DM in the presently used PKC, and that the excessive dietary concentrations of Fe may result in bent legs of lambs (Hidiroglou et al, 1978) and in decreased productivity in dairy cows (Coup and Campbell, 1964), the use of dietary Fe to reduce the bioavailability of dietary Cu was not considered in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that dietary Zn reduced the hepatic Cu accumulation and promoted the formation of relatively non-toxic forms of Cu in the liver, such as metallothionein, which is involved in the storage and detoxification of Cu and other heavy metals (Bremner and Marshall, 1974;Bremner et al, 1976). In the present experiment, the urinary Cu excretion in the Zn-supplemented sheep was almost identical to that of the control group, but the body retention was 26% lower due to the increased fecal Cu excretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation